Analysis of the physical fitness of students in accordance with the norms of the All-Russian sports complex «Ready for labor and defense» with regard to somatic type - E. Kharlamov; S. Orlova; O. Doycheva; E. Osipov; O. Aksenova (Спортивная медицина: наука и практика)
Objective: to detect the relationship between body types (somatotype) and successful passing of the standards of «Ready for Labor and Defense-2014» in students-boys of 18-20 years old. Materials and methods: the study involved 82 male students. The method of somatotyping by Dorokhov RN, Petrukhina VG (1989) was used to determine the body types. The overall and component level of variation was defined. We used the results of passing the test standards and compared them with data on the implementation of the norms of GTO in some types of tests: 100-meters race, 3000-meters race, pulling out from suspension on high bar, standing long jump using double-legged take-off. Results: the muscle mass dominates in all somatic groups, which corresponds to macromuscular type (0,509-0,799). The representatives of microsomatiс type have the highest results - 0.7. When comparing the results of tests of «pulling out from suspension on high bar» with the standards of GTO 2014 6 stage, the best results were found in microsomes group: 90.5% of the subjects completed the specification and received the gold badge, 4.8% of the subjects received the bronze badge, 4.8% of the subjects failed tasks. In mesosomes group only 60% of the subjects fulfilled the standard of «pulling-up» and received the gold badge, 33.33% of the subjects received the silver badge, 6.67% of the subjects did not fulfill the norm. While analyzing the results of «standing long jump using double-legged take-off» more successful results were obtained in the MaC group: 46.67% received the gold badge, 33.33% received the silver badge, 16.67% received the bronze badge, 3.33% did not fulfill the norm. Conclusions: assessing the anthropometric and functional parameters of the organism of students, it is necessary to consider not only the average age range, but also pay attention to the constitutional-typological features.